2023
DOI: 10.1002/smll.202302276
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Drying‐Induced Structural Transformations in a Single Nanocellulose

Abstract: Nanocellulose is attracting attention in the field of materials science as a sustainable building block. Nanocellulose‐based materials, such as films, membranes, and foams, are fabricated by drying colloidal dispersions. However, little is known about how the structure of a single nanocellulose changes during the complex drying process. Here, all‐atom molecular dynamics simulations and atomic force microscopy is used to investigate the structural dynamics of single nanocellulose during drying. It is found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…After the adsorption, the polymer chains were located on both sides of the core CNF and the polymer-grafted CNF exhibited a multimodal height distribution in the cross section (Figure d). Interestingly, the twist of the CNF in the core was relaxed in the course of the adsorption, and the twist angle of the core CNF along the fibril axis (θ twist ) decreased to ∼0.2 °/nm in the final structure (Figure g), while it has been reported that CNFs without surface grafting possess a twisted structure on the mica surface in an MD simulation . These results suggest the polymer brush layer on the both sides of the CNF physically relaxed the twisted structure of the CNF core during the adsorption.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…After the adsorption, the polymer chains were located on both sides of the core CNF and the polymer-grafted CNF exhibited a multimodal height distribution in the cross section (Figure d). Interestingly, the twist of the CNF in the core was relaxed in the course of the adsorption, and the twist angle of the core CNF along the fibril axis (θ twist ) decreased to ∼0.2 °/nm in the final structure (Figure g), while it has been reported that CNFs without surface grafting possess a twisted structure on the mica surface in an MD simulation . These results suggest the polymer brush layer on the both sides of the CNF physically relaxed the twisted structure of the CNF core during the adsorption.…”
Section: Resultsmentioning
confidence: 78%
“…Interestingly, the twist of the CNF in the core was relaxed in the course of the adsorption, and the twist angle of the core CNF along the fibril axis (θ twist ) decreased to ∼0.2 °/nm in the final structure (Figure 2g), while it has been reported that CNFs without surface grafting possess a twisted structure on the mica surface in an MD simulation. 71 These results suggest the polymer brush layer on the both sides of the CNF physically relaxed the twisted structure of the CNF core during the adsorption. The morphology at the water−mica interface was confirmed by in-liquid AFM observation (Figure 3b).…”
Section: ■ Results and Discussionmentioning
confidence: 90%